2021
DOI: 10.11118/actaun.2021.042
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Sustainability: Bioactivity of Leucaena leucocephala Leaves and Pesticide Residue Analysis in Tomato Fruits

Abstract: Field studies were conducted on the application of Leucaena leucocephala leaf extracts as an alternative to carbofuran a synthetic nematicide, while possible residues of carbofuran in tomato fruits were also analysed. Acetone, methanol and petroleum ether fractions of the leaves of L. leucocephala were applied at 200 mg/mL in variants of 100 mL, 150 mL and 200 mL to a naturally nematode infested field. Comparison was made with carbofuran a synthetic insecticide and nematicide. Samples of tomato fruits from car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Moreover, these types of biopesticides do not feature residue problems which are matter of significant concern for consumer and one which this study aims to encourage and explore [21]. Another, field study conducted by [22] on tomato to compared the effect of the application of Leucaena leucocephala leaf extracts as an alternative to carbofuran a synthetic nematicide against the control of nematodes and to look at the pesticide residues (MRLs) after application. The results revealed that pesticide residue (MRLs) was significantly (p = 0.05) higher in plots treated with Carbofuran compared with standard MRLs for Carbofuran in tomatoes.…”
Section: Evaluation New Bio-pesticides and Synthetic Molecules With H...mentioning
confidence: 99%
“…Moreover, these types of biopesticides do not feature residue problems which are matter of significant concern for consumer and one which this study aims to encourage and explore [21]. Another, field study conducted by [22] on tomato to compared the effect of the application of Leucaena leucocephala leaf extracts as an alternative to carbofuran a synthetic nematicide against the control of nematodes and to look at the pesticide residues (MRLs) after application. The results revealed that pesticide residue (MRLs) was significantly (p = 0.05) higher in plots treated with Carbofuran compared with standard MRLs for Carbofuran in tomatoes.…”
Section: Evaluation New Bio-pesticides and Synthetic Molecules With H...mentioning
confidence: 99%
“…are the principal PPNs which affects yield in several crops (Taniwiryonoc et al, 2009;Fabiyi, 2019;Fabiyi and Olatunji, 2021a). Largely, amidst the specie Meloidogyne incognita is a foremost pest of vegetables (Fabiyi and Olatunji, 2021b). Lettuce (Lactuca sativa), a leafy vegetable in the family Asteraceae grown for its leaves which are used in salad preparations is prone to M. incognita infection (William, 2012;de Souza Alonso et al, 2022;Fabiyi, 2022a).…”
Section: Introductionmentioning
confidence: 99%